Effectiveness of a standardized group program intervention for the empowerment of strengths and personal resources - Remor, Eduardo; Amorós Gómez, Montserrat; Carrobles, José Antonio (Anales de Psicología / Annals of Psychology, 2010)
The research aims to evaluate a manualized intervention group program for the empowerment of the psychological resources (PR) and personal strengths for adults, during a period of ten weeks. Different outcome variables was measured as outcome (mood states; PR; perceived stress; dispositional optimism; satisfaction with life; general mental health [depression, anxiety and insomnia, social dysfunction, somatic symptoms]; subjective health complaints). Quasi-experimental design was employed. For the sample A (n=22, Spanish healthy adults) the design was pre-intervention-post and a 3 months follow up, and sample B (n=14, Spanish multiple sclerosis patients) received the same design as sample A; sample C (n=24, Salvadorians healthy adults) design was pre-intervention-post with non-equivalent control group. The results showed a positive effect on mood before and after each session of the program for the three sam-ples (p<.05). In addition, an intervention effect has been identified on the variables optimism, sense of humor, vitality, love and satisfaction with life for Sample A. For Sample B an effect was shown in the variables self-control, social intelligence, stress and subjective health complaints. And for Sample C a greater effect has been shown for the experimental group in relation to the control group for the variables optimism, problems solving, and the global score of PR, and a decrease in stress, depression, and psychosomatic symptoms was shown as well. These results endorse the efficacy of the intervention program employed.